The Role and Use of Non-Saccharomyces Yeasts in Wine Production - Jolly, N.P.; Augustyn, O.P.H.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
The contribution by the numerous grape-must-associated non-Saccharomyces yeasts to wine fermentation has been debated extensively. These yeasts, naturally present in all wine fermentations, are metabolically active and their metabolites can impact on wine quality. Although often seen as a source of microbial spoilage, there is substantial contrary evidence pointing to a positive contribution by these yeasts. The role of non-Saccharomyces yeasts in wine fermentation is therefore receiving increasing attention by wine microbiologists in Old and New World wine producing countries. Species that have been investigated for wine production thus far include those from the Candida, Kloeckera, Hanseniaspora, Zygosaccharomyces, Schizosaccharomyces, Torulaspora, Brettanomyces, Saccharomycodes, Pichia and Williopsis genera. In this review the use and role of non-Saccharomyces yeast in wine production is presented and research trends are discussed.